Behavioral Aspects in Accounting Information System Implementation: Aspek Perilaku dalam Implementasi Sistem Informasi Akuntansi - Rona Shafa Salsabila; Sarwendah Biduri (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Accounting information systems play a central role in supporting organizational financial reporting and decision-making. Specific Background The successful implementation of such systems is not solely determined by technical capability but also by employee behavioral aspects, particularly in companies utilizing integrated systems such as SAP. Knowledge Gap Previous studies report inconsistent findings regarding the role of behavioral aspects in accounting information system practices, and qualitative interpretative evidence remains limited. Aims This study aims to analyze behavioral aspects in the implementation of the accounting information system at PT Sinar Baja Electric and to describe system quality from a behavioral perspective. Results Using primary data collected through interviews and observations and analyzed through qualitative interpretative methods, the study finds that SAP-based accounting information systems are generally implemented well and assist financial management, although operational constraints persist due to limited user competence and delayed data checking. Employee attitudes, perceptions, and emotional control are categorized as good and supportive of system usage. Novelty This study offers interpretative insights based on direct informant perspectives within a manufacturing company context. Implications The findings highlight the importance of strengthening behavioral aspects and continuous training to support reliable and efficient accounting information system practices. Keywords: Behavioral Aspects, Accounting Information Systems, SAP Implementation, Qualitative Interpretative Study, Financial Reporting Key Findings Highlights: Employee attitudes, perceptions, and emotional control support accounting system usage. SAP-based systems assist financial processing but face operational constraints. Behavioral awareness contributes to structured and reliable financial reporting.